2019
DOI: 10.1007/s00334-019-00719-4
|View full text |Cite
|
Sign up to set email alerts
|

Grains from ear to ear: the morphology of spelt and free-threshing wheat from Roman Mursa (Osijek), Croatia

Abstract: Cereals were a significant part of the Roman diet, yet knowledge about their cultivation, distribution and consumption in certain regions is particularly lacking. In Europe, studies generally suggest that from the Iron Age to the Roman period there was a reduction in barley cultivation, an increase in spelt over emmer, a preference for free-threshing wheat over glume wheats, as well as the increased cultivation of rye and oats. Up till now, there was little evidence on crop cultivation in Croatia, but the disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In Dalmatia, millet is rarely found in Roman contexts, although very few sites have been sampled. Of the villa sites, only eight grains of broomcorn millet were recovered from Veli Brijun, four from Osijek-Silos (Reed et al, 2019), and no millet from Danilo (Šoštarić, Küster, 2001;Šoštarić, 2003). Small quantities of millet (Panicum miliaceum) have also been found at the Dalmatian hillfort of Nadin-Gradina (Nye, 1996), the port of Aenona (Gluščević et al, 2006), the pannonian village at Vitrovitica Kiškorija (Šoštarić et al, 2015), and the graves at Ilok and Sćitarjevo (Šoštarić et al, 2006) (Figure 1).…”
Section: Millet Consumption At Lički Ribnikmentioning
confidence: 99%
See 1 more Smart Citation
“…In Dalmatia, millet is rarely found in Roman contexts, although very few sites have been sampled. Of the villa sites, only eight grains of broomcorn millet were recovered from Veli Brijun, four from Osijek-Silos (Reed et al, 2019), and no millet from Danilo (Šoštarić, Küster, 2001;Šoštarić, 2003). Small quantities of millet (Panicum miliaceum) have also been found at the Dalmatian hillfort of Nadin-Gradina (Nye, 1996), the port of Aenona (Gluščević et al, 2006), the pannonian village at Vitrovitica Kiškorija (Šoštarić et al, 2015), and the graves at Ilok and Sćitarjevo (Šoštarić et al, 2006) (Figure 1).…”
Section: Millet Consumption At Lički Ribnikmentioning
confidence: 99%
“…Published deposits of archaeobotanical and zooarchaeological remains dating to the Roman period (1 st -5 th Century AD) in Croatia are still relatively rare. For example, only 12 sites have published archaeobotanical remains (see Reed, 2016 for summary;Essert et al, 2018;Reed, Leleković, 2019;Reed et al, 2019) and only three of these are from villa sites: the 3 rd -4 th century AD rural villa at Danilo, Dalmatia (Šoštarić, 2003), the 1 st -5 th century AD rural villa at Veli Brijun, Istria (Šoštarić, Küster, 2001), and the 2 nd -4 th century AD urban villa of Osijek-Silos (Reed et al, 2019). Faunal data are even more underrepresented and only five Roman period sites being published in Croatia (Alvàs -Marion, 2001;Brajković, Paunović, 2001;Campadelli, 2007;Miculinić, 2018;Šimić-Kanaet et al, 2005;Šoštarić et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental research has shown that plants experiencing physiological stress from differences in water availability, ambient temperature, or amount of nutrients during grain filling resulted in grain size diminution, due to interference in the deposition of carbohydrates in the grains [37–42]. In addition, Reed [43] also showed that grains from a single ear of spelt wheat exhibited a wide variety of sizes, indicating that variability in grain size can also be due to heterogeneous ripening times of grains on the ear.…”
Section: Discussionmentioning
confidence: 99%
“…They come from single-grained spikelets. Among spelt grains, some 'stunted' grains were also observed in the archaeobotanical samples in the region (Reed et al, 2019). They are half the size of the other grains but are almost fully formed with the typical morphological shape of T. spelta.…”
mentioning
confidence: 80%